«Стаю урбаністом, не можу без міста…» (місто і людина в поетичному дискурсі ХХ століття) - Сюта, Г. (Культура слова, 2021)
У контексті активного розвитку теми міста в українській літературі, що був зумовлений соціокультурними чинниками й інтелектуальними запитами доби від кінця ХІХ ст., формується новий – урбаністичний – тип світосприймання і відповідна йому урбаністична картина світу з ядерним макроконцептом місто. Із цими змінами скорельовані трансформації пр инципів і засобів мовоопису міста, переміщення акцентів із характерного для класичної літератури змалювання типових або унікальних міських пейзажів і картин побуту на масштабне відтворення багатовимірного соціально-культурного урбанотексту. При цьому незмінно центральною й актуальною для осмислення залишається проблема «взаємовідношення» міста і людини (ставлення людини до міста, впливу міста на людину тощо). Місто в поетичному дискурсі ХХ ст. – це поліаспектне середовище, в якому формується відмінний від традиційно-патріархального соціально-психологічний тип особистості. Життя цієї особистості може бути гармонізоване з життям міста або ж протиставлене йому. Трактування міста як штучного, не гармонізованого з жит тям людини і природи простору – це своєрідний ментальний рефлекс традиційної для української літератури опозиції «село / природа – місто». В асоці ативно-семантичному розвитку ключових понять цієї опозиції протиставляються ознаки «духовне – бездуховне», «природне – штучне», «традиційне – модерне», «давнє – сучасне», «національне – денаціоналізоване». Знакова реалізація образу місто – його показ як механізовано-прагматичного середовища, де відбувається моральна деградація і знеособлення людини. Загальну картину такого негативного показу доповнюють поетичні описи буття людини в місті, в яких домінують семи ‘аморальність’, ‘байдужість’, ‘самотність’, ‘розгубленість’. Позитивний аспект стосунків людини і міста спостережено в контексті вербалізації мотиву інтегрованості людини в життя міста, коли людина почувається органічною частиною урбанопростору. The image of the city is relevant for the national linguоculture in its various genre-style and aesthetic varieties. Ways of its verbalization in different poetic texts testify to the dynamics of Ukrainian artistic thinking. Since the end of 19 th century, the theme of the city in Ukrainian literature, especially in poetry, has been developing with significant intensity, while the interpretation of the village as a bearer of established ethnocultural stereotypes is gradually losing its relevance. As a result, a new urban type of worldview and the corresponding urban picture of the world with a nuclear macroconcept of the city are formed. These changes are correlated with the transformation of approaches to the linguistic description of the city, the shift of emphasis from the typical for classical literature depiction of urban landscapes, typical or unique urban topos to large-scale reproduction of multidimensional socio-cultural urban text. At the same time, the problem of the relationship between the city and man (the attitude of man to the city, the influence of the city on man, etc.) remains invariably central. The world of the city in the poetic discourse of the XX th century is an environment of a new multifaceted human life (geographical / industrial / educational / informational / social / domestic / personal space). And in this world is formed different from the traditional patriarchal, sociopsychological type of personality. The life of this personality can be harmonized with the life of the city or opposed to it. The interpretation of the city as an artificial space, not harmonized with human life and nature, is a logical continuation of the traditional for Ukrainian literature opposition «village / nature – city». In the paradigmatic development of the key concepts of this opposition the signs of spiritual – unspiritual, natural – artificial, traditional – modern, national – denationalized are contrasted. Important realization of the image of the city – its display as a space of immorality, destructive environment, where there is a moral degradation and depersonalization of man. The general picture of such a negative display of the city is complemented by poetic descriptions of human existence in urban space, which are dominated by senses ‘indifference’, ‘loneliness’, ‘confusion’ and so on. The positive aspect of the relationship between man and the city, human life in the city is observed in the context of verbalization of the motive of human integration into city life, when a person feels an organic part of urban space.